464 Use of titanium dioxide as a marker for determining fecal output in horses. (7th December 2018) - Fowler, A; Pyles, M; Hayes, S; Crum, A; Bill, V; Lawrence, L
Abstract: External markers, such as titanium dioxide (TiO2 ), allow for spot samples to be used to estimate fecal output (FO) in place of total fecal collections (TFC) for digestibility studies. The use of TiO2 to determine FO has not been thoroughly evaluated in horses. To investigate the accuracy of TiO2 in estimating FO, 15 mature horses were divided into 3 groups fed diets varying in forage:concentrate. HIGH was fed 95% forage, MED was fed 73% forage, and LOW was fed 45% forage. Daily rations were split into 3 equal meals spaced 8 h apart. Each meal was thoroughly mixed and 2 g TiO2 /kg DM was incorporated. Horses were fed these diets for a minimum of 12 d and then a 5 d TFC was performed. Actual daily FO was recorded for each horse and spot fecal samples were collected every 4 h from each horse for measurement of TiO2 and calculation of FO. Treatments were compared using repeated measures ANOVA. Actual and calculated FO were compared using linear regression. Fecal recovery of TiO2 averaged 106%.When averaged across all 5 d, calculated FO was 95 ± 15% accurate in predicting actual FO in HIGH, 98 ± 18% accurate for MED, and 101 ± 33% accurate for LOW (P > 0.05); accuracies were not different from 100% (P > 0.05). The relationship between actual and calculated FO across all treatments was significant but weak (R 2 = 0.0489) and the slope was 0.33. Titanium dioxide concentrations in spot samples did not remain constant over time and appeared to vary with respect to meal feeding. Overall, TiO2 may not be useful in horses if the goal is to use one fecal sample to estimate daily FO. However, frequent spot samples over 5 d may collectively be able to estimate average FO.